Resisting a Restrictive Discourse Policy - Ondine Gage (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
A survey, an interview with a remarkable teacher, and an analysis of classroom interactions reveal strategies for countering federal and state policies against students’ right to their own language.